Tantangan dan Solusi dalam Transfortasi Tak Seimbang Menuju Efisiensi Logistik - Pesta Gultom; Fery Wahyudi; Almunawar Almunawar; Firdan Hidayat; Okta Feryanus Tarigan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Unbalanced transportation is one of the main challenges in logistics that can affect efficiency and operational costs. The imbalance between supply and demand can cause high transportation costs, delays in delivery, and decreased product quality. Therefore, it is necessary to analyze and develop solutions to overcome the challenges of unbalanced transportation and improve logistics efficiency. This study aims to identify the challenges and solutions of unbalanced transportation towards logistics efficiency. This study is expected to contribute to the development of unbalanced transportation solutions and improve logistics efficiency.